African Art needs to Come Home - and this is why - Dilip, Ratha; Kabanda, Patrick (The Guardian, 2015)
African art dots museums across Europe and North America, gracing countries where many Africans would be hard pressed to get a visa. In the Neues museum in Berlin, the bust of Queen Nefertiti is lit and kept at a temperature to mimic conditions in Egypt. Its grace radiantly reflects the meaning of her name: “the beautiful one has come.” For Egypt and Africa, however, the beautiful one left. Nefertiti has been in Germany since 1913, despite the fact Egypt has demanded she be returned home.